'When dealing with space and time, you will not only deal with space and time' (KULT_online, 2012)
In his monograph Raum-Zeit (Space-Time), which was published in the de Gruyter series Grundthemen der Philosophie (Basics in Philosophy), Martin Carrier analyses the phenomena of space and time by interpreting findings of the natural sciences from a philosophical point of view. The reader gains deep insights into elusive phenomena such as the course of time or the relation of space and time towards bodies and events. This can, however, only be achieved if one has sufficient knowledge of physics or mathematics.